COMPARISON OF Mo COATING DEPOSITED BY TWAS AND APS SinplexPro THERMAL SPRAY TECHNIQUES - Šárka Houdková; Jakub Antoš; Petra Šulcová; Kateřina Lencová; Jan Hajšman; Karolína Burdová; Josef Duliškovic (Acta Polytechnica CTU Proceedings, 2020)
The wear resistant Mo coatings were deposited using SmartArc Electric Arc Wire Spray System and advanced SinplexPro high throughput atmospheric plasma spray gun. The coatings were analyzed in terms of microstructure, mechanical properties and tribological characteristics, including wear rate and wear mechanism. It was shown that despite of the differences in deposition process principles, the properties of the coatings don’t differ with respect to their functional properties. Both coatings reached comparable hardness, microhardness, wear resistance and coefficient of friction. The economic aspects remain the main argument for the recommendation of the most suitable thermal spray deposition technique for the application of molybdenum coatings.